If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-97=-1-4(3x+3)
We move all terms to the left:
-97-(-1-4(3x+3))=0
We calculate terms in parentheses: -(-1-4(3x+3)), so:We get rid of parentheses
-1-4(3x+3)
determiningTheFunctionDomain -4(3x+3)-1
We multiply parentheses
-12x-12-1
We add all the numbers together, and all the variables
-12x-13
Back to the equation:
-(-12x-13)
12x+13-97=0
We add all the numbers together, and all the variables
12x-84=0
We move all terms containing x to the left, all other terms to the right
12x=84
x=84/12
x=7
| 98x-70=14(7x-5) | | 11x+4=128 | | (3x−17)=(2x−23) | | 3.14x=18.84 | | 6-x=7x-10x-15 | | -97=-1-4(3x=3) | | 19,5x+10=-0.5x+4 | | 10z-6=-4+8z+4 | | 1a+-3=2a+3 | | 4−–r=6 | | 21=4w-3 | | -7x+12=4x+45 | | -4y/8-3y=0 | | 100-3=3n-10+5n+21 | | 2(x3)=-8 | | 4y-3-9y=32* | | 3.25x+1+8.5x-2=5.5x+3+8x | | -2=16-6x | | -31=5z-14 | | 2(x-2)2-5=45 | | 00-5x=140-10x | | 10-4y/8-3y=-10 | | c^2-6c=18 | | 4x+2x-6=6x-6 | | 11/3=31/9y | | 27+9d-7d+3=2 | | 10m+15-5m=35 | | (x-30)+(x-30)+42=180 | | -4-6h=10-8h | | x^-6=636 | | 27+9d-7d+3=2 | | 0+24x=74+20x |